2005
DOI: 10.4314/jasem.v8i1.17222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Cadmium Exposure on Renal Glomerular and Tubular Functions in the Rat

Abstract: ABSTRACT:The effects of orally consumed cadmium on the functions of the kidney have been investigated in rats based on the reported level of the toxicant in Warri River. Relative to the corresponding controls there were significant (P < 0.05) increases in the amount of cadmium in the kidneys of rats in all the test groups. Biochemical analysis revealed significant (P < 0.05) changes in plasma creatinine after 2 months (control -1.20 ± 0.20 × 10 −2; test -0.92 ± 0.26 × 10 −2 µg/ml) and glucose after 1-month (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…This goes along with the findings of Asagba and Obi[17] that cadmium toxicity brings about a reduction in 24 hour Urine Volume. This is because cadmium (as well as most other heavy metals) interferes with glomerular filtration rate (GFR) and tubular processes (tubular re-absorption and tubular secretion)[18] which are the major determinants of Urine Volume.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This goes along with the findings of Asagba and Obi[17] that cadmium toxicity brings about a reduction in 24 hour Urine Volume. This is because cadmium (as well as most other heavy metals) interferes with glomerular filtration rate (GFR) and tubular processes (tubular re-absorption and tubular secretion)[18] which are the major determinants of Urine Volume.…”
Section: Discussionsupporting
confidence: 85%
“…Table 3 shows that there was no significant difference in 24 hour urine volume of animals pretreated with onion before cadmium administration and the control, while there was significant ( P > 0.05) reduction in animals treated with cadmium only. This goes along with the findings of Asagba and Obi[ 17 ] that cadmium toxicity brings about a reduction in 24 hour Urine Volume. This is because cadmium (as well as most other heavy metals) interferes with glomerular filtration rate (GFR) and tubular processes (tubular re-absorption and tubular secretion)[ 18 ] which are the major determinants of Urine Volume.…”
Section: Discussionsupporting
confidence: 85%
“…Zinc is a cofactor essential for ALP function and with zinc displacement ALP synthesis and function is compromised (Suzuki et al, ). Compared to the control, creatinine levels were significantly lower in the metal combination group and may indicate renal tubular dysfunction (Asagba & Obi ; Babaknejad, Moshtaghie, Shahanipour, & Bahrami, ). Several researchers have also reported lower ALP and creatinine levels after exposed to Cr (Kumar & Kumar, ; Kumar, Rana, & Prakash, ).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies by this author has shown that the crude methanol extract (Me70) had a significantly higher concentration of bioactive principles with antioxidant properties such as phenols, flavonoids and alkaloids as well as strong reducing powers and scavenging potential against unstable atoms in vitro than the aqueous extract, non-toxic at 100 mg/kg bwt [ 11 , 12 ]. Asagba and Obi [ 13 ] had previously reported that drinking-water contaminated with 0.3 mg Cd/L can cause alterations in major biochemical indices of experimental rats. In the absence of documented scientific data on the potential of Geophila obvallata in literature, this research explored the protective effect of Me70 and its fractions in reversing cadmium-induced nephrotoxicity in male Wistar rats.…”
Section: Introductionmentioning
confidence: 99%